Research on the development of integration clusters of strategic emerging industries in Jiangxi - Wang Hui; Zhang Siqi (ITM Web of Conferences)
This thesis studies the relationship between the integrated cluster development ofstrategic emerging industries and cross-border e-commerce in Jiangxi Province, and puts forwardthe optimization countermeasures to promote the integrated development of cross-bordere-commerce in jiangxi Province. Cross-border e-commerce, as one of the strategic emergingindustries,has attracted much attention. Connecting global buyers and sellers throughe-commerce platforms provides a broad opportunity for enterprises to expand the internationamarket. In the context of the intelligent era, this study explores the application potential andpromotion role of intelligent technology in the integrated development of cross-bordere-commerce. By building an online integrated service platform, constructing an inteligentlogistics system, guiding the transformation and upgrading of traditional industries and otheroptimization measures, it can promote the integrated development of cross-border e-commercein jiangxi Province, and promote the upgrading and transformation of strategic emergingindustries. This study is of great significance for promoting the economic development andenhancing the industrial competitiveness of Jiangxi Province.